Certification and market transparency - Konrad Stahl; Roland Strausz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
We provide elementary insights into the effectiveness of certification to increase market transparency. In a market with opaque product quality, sellers use certification as a signaling device, while buyers use it as an inspection device. This difference alone implies that seller-certification yields more transparency and higher social welfare. Under buyer-certification profit maximizing certifiers further limit transparency, but because seller-certification yields larger profits, active regulation concerning the mode of certification is not needed. These findings are robust and widely applicable to, for instance, patents, automotive parts, and financial products.
Keywords: D82; G24; L15; 330; Market Transparency; Certification; Information and Product Quality; Asymmetric Information